Electronic reporting of integrated disease surveillance and response: lessons learned from northeast, Nigeria, 2019 - Luka Mangveep Ibrahim; Ifeanyi Okudo; Mary Stephen; Opeayo Ogundiran; Jerry Shitta Pantuvo; Daniel Rasheed Oyaole; Sisay Gashu Tegegne; Abdelrahim Khalid; Elsie Ilori; Olubunmi Ojo; Chikwe Ihekweazu; Fiona Baraka; et al. (BMC, 2021)
Abstract Background Electronic reporting of integrated disease surveillance and response (eIDSR) was implemented in Adamawa and Yobe states, Northeastern Nigeria, as an innovative strategy to improve disease reporting. Its objectives were to improve the timeliness and completeness of IDSR reporting by health facilities, prompt identification of public health events, timely information sharing, and public health action. We evaluated the project to determine whether it met its set objectives. Method We conducted a cross-sectional study to assess and document the lessons learned from the project. We reviewed the performance of the local government areas (LGAs) on timeliness and completeness of reporting, rumors identification, and reporting on the eIDSR and the traditional paper-based system using a checklist. Respondents were interviewed online on the relevance, efficiency, sustainability, project progress and effectiveness, the effectiveness of management, and potential impact and scalability of the strategy using structured questionnaires. Data were cleaned, analyzed, and presented as proportions using an MS Excel spreadsheet. Responses were also presented as direct quotes. Results The number of health facilities reporting IDSR increased from 103 to 228 (117%) before and after implementation of the eIDSR respectively. The timeliness of reporting was 43% in the LGA compared to 73% in health facilities implementing eIDSR. The completeness of IDSR reports in the last 6 months before the evaluation was ≥85%. Of the 201 rumors identified and verified, 161 (80%) were from the eIDSR pilot sites. The majority of the stakeholders interviewed believed that eIDSR met its predetermined objectives for public health surveillance. The benefits of eIDSR included timely reporting and response to alerts and disease outbreaks, improved timeliness, and completeness of reporting, and supportive supervision to the operational levels. The strategy helped stakeholders to appreciate their roles in public health surveillance. Conclusion The eIDSR has increased the number of health facilities reporting IDSR, enabled early identification, reporting, and verification of alerts, improved timeliness and completeness of reports, and supportive supervision of staff at the operational levels. It was well accepted by the stakeholder as a system that made reporting easy with the potential to improve the public health surveillance system in Nigeria.